Natural History of Cervical Intraepithelial Neoplasia-2 in HIV-Positive Women of Reproductive Age. (15th December 2018) - Colie, Christine; Michel, Katherine G.; Massad, Leslie S.; Wang, Cuiwei; D'Souza, Gypsyamber; Rahangdale, Lisa; Flowers, Lisa; Milam, Joel; Palefsky, Joel M.; Minkoff, Howard; Strickler, Howard D.; Kassaye, Seble G.
Abstract : Objective: To evaluate the natural history of treated and untreated cervical intraepithelial neoplasia-2 (CIN2) among HIV-positive women. Methods: Participants were women enrolled in the Women's Interagency HIV Study between 1994 and 2013. One hundred four HIV-positive women diagnosed with CIN2 before age 46 were selected, contributing 2076 visits over a median of 10 years (interquartile range 5–16). The outcome of interest was biopsy-confirmed CIN2 progression, defined as CIN3 or invasive cervical cancer. CIN2 treatment was abstracted from medical records. Results: Most women were African American (53%), current smokers (53%), and had a median age of 33 years at CIN2 diagnosis. Among the 104 HIV-positive women, 62 (59.6%) did not receive CIN2 treatment. Twelve HIV-positive women (11.5%) showed CIN2 progression to CIN3; none were diagnosed with cervical cancer. There was no difference in the median time to progression between CIN2-treated and CIN2-untreated HIV-positive women (2.9 vs. 2.7 years, P = 0.41). CIN2 treatment was not associated with CIN2 progression in multivariate analysis (adjusted hazard ratio 1.82; 95% confidence interval: 0.54 to 7.11), adjusting for combination antiretroviral therapy and CD4 + T-cell count. In HIV-positive women, each increase of 100 CD4 + T cells was associated with a 33% decrease in CIN2 progression (adjusted hazard ratio 0.67; 95% confidence interval: 0.47 to 0.88), adjusting for CIN2 treatment and combination antiretroviral therapy. Conclusions: CIN2 progression is uncommon in this population, regardless of CIN2 treatment. Additional studies are needed to identify factors to differentiate women at highest risk of CIN2 progression. Abstract : Supplemental Digital Content is Available in the Text.